The Biological Functions and Clinical Values of Exosomal Circular RNAs in Hepatocellular Carcinoma - Zhao, Ying; Yao, Jinmei (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) exacts a heavy disease burden and is currently the second most common cause of cancer-related deaths worldwide. HCC usually lacks obvious symptoms in the early stage, and most HCC patients are diagnosed at advanced stages with poor prognosis. Circular RNAs (circRNAs) are single-stranded RNAs that form covalently closed loops and are stable in exosomes. Exosomes are known as important messengers of the cross-talk between tumor and immune cells. Accumulating studies have demonstrated the promoter or suppressor roles of exosomal circRNAs in the carcinogenesis, progression, and metastasis of HCC. In this review, we summarized the current studies on the biological functions and diagnostic and prognostic values of exosomal circRNAs in HCC progression.